Pharmaceutical Pollution: Azole Antifungal Drugs and Resistance of Opportunistic Pathogenic Yeasts in Wastewater and Environmental Water - Mzimkhulu E. Monapathi; Joseph C. Oguegbulu; Lilian Adogo; Michael Klink; Bamidele Okoli; Fanyana Mtunzi; Johannes S. Modise (Applied and Environmental Soil Science)
The occurrence of residual antifungal agents through indiscriminate prophylactic use and inappropriate disposal has been reported in wastewater treatment plants (WWTPs), surface water, and groundwater environments. Opportunistic pathogenic aquatic yeasts develop resistance to commonly used antifungal agents through continued exposure to residual antifungal agents in environmental waters. This poses a major public health concern. The present review attempts to provide a brief description of antifungal drugs, with a focus on the most widely used class of antifungal drugs, the azoles, as emerging contaminants in environmental water. Routes of exposure of azole antifungal drugs in wastewater treatment plants, surface water, and groundwater are discussed. The presence of pathogenic yeasts in environmental water, the associated azole resistance, and the risk of exposure to humans and microbiota are highlighted. Management actions needed to curtail the spread and minimise the risks are also indicated. Further research on the occurrence of antifungal agents in wastewater and environmental water is vital to better understand and mitigate the associated health-related risks.